A apreciação musical infantil: aspectos da constituição da infância contemporânea no discurso de crianças do Ensino Fundamental - Macedo, Narjara Medeiros de (2005)
Music can be found in peculiar historical and social context with distinct functions, such as religious rituals, ethic-esthetic education of subjects, therapeutic elements, critic and maintenance of established patterns, among others. Considered as language, music acts on dialogue dimensions of the body, the senses, the affectionate-cognitive and of social interactions. Their uses reveal the social forces that cross the culture and constitution of subjectivities. The attribution of senses by the subjects to musical production reveals the cultural voices in dialogue, that circumscribe determined social places to them. Our aim in this work is to investigate the child musical appreciation, with children about 7 to 9 years old, and, by attributing uses and senses to music, unveil the voices that settle the places intended and assumed by infancy in contemporaneity The child constructs its musical appreciation through cultural access and mediation, possible by circulation in several socializing groups like family, school, church, infant groups, community groups and, more recently, publicity and media These last two spheres, enabled by the development of the technological means of communication, contributed to the dissemination of the set of consume ideas and for the emergence of the cultural industry, characteristic of the capitalistic production way in its present configuration. They develop new possibilities of perception of the world, in which the limits between childhood and adulthood are not anymore the same that have been established in previous centuries. So, the child musical appreciation is constituted by homogeneity regarding the senses built and disseminated by cultural industry and by the logical merchandizing, and singularities, associated to the construction of senses in interaction with global, local, and multiple contexts, through which the subject circulates and constitutes himself polyphonically